(Invited) Display and LSI Applications of Oxide Semiconductor LSIs (OS LSIs) Using Crystalline In–Ga–Zn Oxide (IGZO): Applications Related to Coronavirus COVID-19 Pandemic. (8th September 2020) - Onuki, Tatsuya; Okamoto, Yuki; Aoki, Takeshi; Matsuzaki, Takanori; Kozuma, Munehiro; Kunitake, Hitoshi; Motoyoshi, Ryosuke; Kimura, Hajime; Yamane, Yasumasa; Sasagawa, Shinya; Yamazaki, Shunpei
Abstract : This paper shows structures and features of a field-effect transistor (FET) fabricated using a c-axis aligned crystalline In–Ga–Zn oxide (CAAC-IGZO), which is a typical example of crystalline oxide semiconductor (OS) ceramics, as a channel material, and applications of the CAAC-IGZO FET up to this point. In this study, we propose an AI accelerator as novel LSI using an OS (OS LSI) and make a detail description of the AI accelerator.